2007
DOI: 10.1016/j.seizure.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Retention rate of Levetiracetam in children with intractable epilepsy at 1 year

Abstract: Our results confirm the efficacy and tolerability of LEV in children with refractory epilepsies and demonstrate good response and retention rates at 12 months. It represents the largest cohort of paediatric patients published so far on LEV with a 1-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 22 publications
2
23
1
9
Order By: Relevance
“…Grosso et al reported that 31% of their patients after three months and 15% after 12 months were seizure free (15). Peake et al reported 14% seizure free patients after two and six months and 5% after 12 months (14). According to the results of these studies, it can be concluded that duration of follow-up is influenced by the percentage of patients being seizure free.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Grosso et al reported that 31% of their patients after three months and 15% after 12 months were seizure free (15). Peake et al reported 14% seizure free patients after two and six months and 5% after 12 months (14). According to the results of these studies, it can be concluded that duration of follow-up is influenced by the percentage of patients being seizure free.…”
Section: Discussionmentioning
confidence: 95%
“…Grosso et al (15) and Peake et al (14) found a decrease in the number of patients being seizure free during follow-up. Grosso et al reported that 31% of their patients after three months and 15% after 12 months were seizure free (15).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Положительный эффект достиг-нут в 60 % случаев. Процент удержания на терапии через 1 год составил 49 % (с учетом того, что исследо-вание включало только детей с тяжелыми резистент-ными формами эпилепсии, данный показатель очень высок) [77].…”
Section: детской неврологииunclassified
“…[2] Yeni AEİ'lardan levetirasetamın çocuk ve erişkinlerin parsiyel başlangıçlı, idiyopatik ya da jeneralize nöbetlerindeki etkinliği ve gü-venirliği kabul edilmesine rağmen, yenidoğanda özellikle prematürelerde kullanımı ile ilgili sınırlı çalışma vardır. [3,4] Bu yazıda klasik AEİ'lara cevap vermeyen dirençli nöbetleri olan yedi günlük ikiz prematüre olgularda LEV'yi kullanma sonuçlarımız sunuldu.…”
Section: Introductionunclassified